The Effect of Compensation on Performance with Job Satisfaction as a Mediating Variable in Grab Drivers in Blitar City - Kukuh, Catur; Ambarwati, Titiek; Febriani, Rizki Febriani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to analyze how the effect of compensation on performance with job satisfaction as a mediating variable in the Blitar city grab driver. The sampling technique used incidental sampling with a sample of 100 drivers. Data collection techniques using a questionnaire. The data analysis technique used path analysis with the SPSS program. The results showed that compensation had a positive and significant effect on performance, compensation had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on performance, and compensation had no positive and significant effect on performance as a mediation.